Preliminary Extracellular Vesicle Profiling in Drainage Fluid After Neck Dissection in OSCC - Wang, J; Man, Q-W; Fu, Q-Y; Zhong, N-N; Wang, H-Q; Li, S-R; Gao, X; Lin, H; Su, F-C; Bu, L-L; Chen, G; Liu, B (Journal of dental research, 2023)
Lymph node metastasis is related to poor prognosis in oral squamous cell carcinoma (OSCC), and few studies have explored the relevance of postoperative drainage fluid (PDF) in metastasis. Extracellular vesicles (EVs) are nanosized vesicles that can transfer oncogenic molecules to regulate tumorigenesis. However, the proteomic profile of postoperative drainage fluid-derived EVs (PDF-EVs) in OSCC has not been elucidated. Herein, we collected drainage fluid from OSCC patients after neck dissection to investigate the difference in PDF-EVs between patients with metastatic lymph nodes (the LN+ group) and nonmetastatic lymph nodes (the LN- group). The proteomic profile of PDF-EVs from the LN+ and LN- groups was compared using label-free liquid chromatography tandem-mass spectrometry-based protein quantification. The results revealed that PDF-EVs were mainly derived from epithelial cells and immune cells. A total of 2,134 proteins in the PDF-EVs were identified, and 313 were differentially expressed between the LN+ and LN- groups. Metabolic proteins, such as EHD2 and CAVIN1, were expressed at higher levels in the LN+ group than in the LN- group, and the levels of EHD2 and CAVIN1 in the postoperative drainage fluid were positively correlated with lymph node metastasis. Our study revealed previously undocumented postoperative drainage fluid-associated proteins in patients with metastatic OSCC, providing a starting point for understanding their role in metastatic and nonmetastatic OSCC.